Emerging Therapeutics for Immune Tolerance: Tolerogenic Vaccines, T cell Therapy, and IL-2 Therapy - Moorman, Cody D.; Sohn, Sue J.; Phee, Hyewon (Frontiers in Immunology, 2021)
Autoimmune diseases affect roughly 5-10% of the total population, with women affected more than men. The standard treatment for autoimmune or autoinflammatory diseases had long been immunosuppressive agents until the advent of immunomodulatory biologic drugs, which aimed at blocking inflammatory mediators, including proinflammatory cytokines. At the frontier of these biologic drugs are TNF-α blockers. These therapies inhibit the proinflammatory action of TNF-α in common autoimmune diseases such as rheumatoid arthritis, psoriasis, ulcerative colitis, and Crohn’s disease. TNF-α blockade quickly became the “standard of care” for these autoimmune diseases due to their effectiveness in controlling disease and decreasing patient’s adverse risk profiles compared to broad-spectrum immunosuppressive agents. However, anti-TNF-α therapies have limitations, including known adverse safety risk, loss of therapeutic efficacy due to drug resistance and lack of efficacy in numerous autoimmune diseases, including multiple sclerosis. The next wave of truly transformative therapeutics should aspire to provide a cure by selectively suppressing pathogenic autoantigen-specific immune responses while leaving the rest of the immune system intact to control infectious diseases and malignancies. In this review, we will focus on three main areas of active research in immune tolerance. First, tolerogenic vaccines aiming at robust, lasting autoantigen-specific immune tolerance. Second, T cell therapies using Tregs (either polyclonal, antigen-specific, or genetically engineered to express chimeric antigen receptors) to establish active dominant immune tolerance or T cells (engineered to express chimeric antigen receptors) to delete pathogenic immune cells. Third, IL-2 therapies aiming at expanding immunosuppressive regulatory T cells in vivo.